In Vitro Methods to Characterize the Effects of Tobacco and Nontobacco Products on Human Platelet Function. Issue 1 (24th May 2018) - Loelius, Shannon G.; Spinelli, Sherry L.; Lannan, Katie L.; Phipps, Richard P.
Abstract: In this document, we describe methods for the isolation, treatment, and functional testing of human blood platelets in vitro . Functional assays for inflammatory function include flow cytometry and immunoassays for platelet release of platelet factor 4, soluble CD40L, prostaglandin E2, and thromboxane. Assays for platelet hemostatic function described here examine platelet spreading, aggregation using platelet‐rich plasma, and thromboelastography. Also described here are methods for testing cigarette smoke on primary human platelets in vitro, which our lab developed to address a major knowledge gap regarding how cigarette smoke dysregulates platelets and how this platelet dysregulation contributes to cardiovascular disease. Some of these protocols may be repurposed for investigation of the toxicity potential of other tobacco products and environmental insults. © 2018 by John Wiley & Sons, Inc.